2016
DOI: 10.1177/1029864916631034
|View full text |Cite
|
Sign up to set email alerts
|

Creativity beyond innovation: Musical performance and craft

Abstract: While creativity has been defined in a multiplicity of ways across disciplines, scholars generally agree that it involves the generation of ideas or products that are novel, of value, and appropriate to the field. Yet by too readily connecting creativity in musical performance to innovation, does this model neglect the more inconspicuous and Op. 28 (1969). My argument draws attention to "everyday" aspects of music-making, in which musicians make decisions in engaging with their work which are less explicit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Riley et al 2013). The patterning of the activities provides opportunities for sensory and aesthetic engagement, and allows participants to express their own creativity within a structure in a similar way to that uncovered by Payne for music performance (Payne 2016). Both activities also provide opportunities to connect to others, through the activity itself in group settings (cf.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Riley et al 2013). The patterning of the activities provides opportunities for sensory and aesthetic engagement, and allows participants to express their own creativity within a structure in a similar way to that uncovered by Payne for music performance (Payne 2016). Both activities also provide opportunities to connect to others, through the activity itself in group settings (cf.…”
Section: Discussionmentioning
confidence: 97%
“…The current study thus compares two different creative activities, knitting and music-making, which are relatively popular amongst adults of all ages (Stannard and Sanders 2015;ABRSM 2014). In common, both knitting and musicmaking can be undertaken alone or in a group, accessed relatively simply but also requiring skill to achieve higher technical levels (Stanley 2002;Perkins and Williamon 2014); involve sequenced physical actions (Riley et al 2013;Repp and Su 2013); follow existing patterns (patterns or scores) while also allowing for creativity in interpretation or originality (Stannard and Sanders 2015;Payne 2016); embody emotion through physical interaction with artefacts (Pöllänen 2009;Lamont 2012); provide 'therapeutic' potential (Reynolds and Prior 2006;Fachner 2014), the opportunity to build identity (Howie et al 2004;Lamont 2011), and potential for social connections (Reynolds 2009;Pearce et al 2015). However, there are some differences.…”
mentioning
confidence: 99%
“…Whilst composition and improvisation can be seen as paradigmatic generative processes (Lothwesen & Lehmann, 2017, p. 342), reproductive and perceptive activities like performing music (Clarke, 2012; Rink, 2002) and listening to music (Hargreaves, Hargreaves, & North, 2012; Webster, 2002) are also considered to be creative (Hargreaves, MacDonald, & Miell, 2012, p. 3). Musical performance research has shown that a creative process might be shared among the members of an ensemble (Payne, 2016; Sawyer, 2006; Schober & Spiro, 2014). Moreover, elements of the creative process might also be distributed according to the typical characteristics of musical genres.…”
Section: Approaching Creativity In Musicmentioning
confidence: 99%
“…Studies of creativity typically concentrate on general aspects of creativity common to all artistic domains or on elements particular to a given domain (Kaufman and Baer, 2005 ; Kaufman and Sternberg, 2010 ). Creativity in music performance was first studied with respect to improvisation (Clarke, 1988 , 2012 ; Pressing, 1988 ; Kenny and Gellrich, 2002 ) and, more recently, with respect to music interpretation (Lisboa et al, 2011 ; Héroux and Fortier, 2014 ; Héroux, 2016 ; Payne, 2016 ; Barros et al, 2017 ; Wise et al, 2017 ). As Clarke ( 2012 ) notes, identifying creative elements in the interpretation of written music is not an easy task.…”
Section: Introductionmentioning
confidence: 99%
“… Various studies have been conducted to understand the role of mental representation when musicians practice or perform music (Lehman and Ericsson, 1997 ; Sloboda, 2005 ) and the work steps required for a musician to prepare a concert (Chaffin et al, 2003 ). More recent studies examine creativity in the shaping of a musical interpretation (Lisboa et al, 2011 ; Payne, 2016 ; Barros et al, 2017 ; Wise et al, 2017 ). However, none of these studies answers the following questions: Why do expert musicians working from the same score create different musical interpretations?…”
mentioning
confidence: 99%